Effects of hypoxia-inducible factor-prolyl hydroxylase inhibitors vs. erythropoiesis-stimulating agents on iron metabolism in non-dialysis-dependent anemic patients with CKD: A network meta-analysis - Yang, Junlan; Xing, Jie; Zhu, Xiaodong; Xie, Xiaotong; Wang, Lina; Zhang, Xiaoliang (Frontiers in Endocrinology, 2023)
Objective: To compare the effects of five hypoxia-inducible factor-prolyl hydroxylase domain inhibitors (HIF-PHIs), two erythropoiesis-stimulating agents (ESAs), and placebo on iron metabolism in renal anemia patients with non-dialysis-dependent chronic kidney disease (NDD-CKD). Method: Five electronic databases were searched for studies. Randomized controlled clinical trials comparing HIF-PHIs, ESAs, and placebo in NDD-CKD patients were selected. The statistical program used for network meta-analysis was Stata/SE 15.1. The main outcomes were the change in hepcidin and hemoglobin (Hb) levels. The merits of intervention measures were predicted by the surface under the cumulative ranking curve method. Results: Of 1589 original titles screened, data was extracted from 15 trials (3228 participants). All HIF-PHIs and ESAs showed greater Hb level-raising ability than placebo. Among them, Desidustat demonstrated the highest probability of increasing Hb (95.6%). Hepcidin (MD=-43.42, 95%CI: -47.08 to-39.76), ferritin (MD=-48.56, 95%CI: -55.21 to-41.96) and TSAT (MD=-4.73, 95%CI: -5.52 to-3.94) were decreased, while transferrin (MD=0.09, 95%CI: 0.01 to 0.18) and TIBC (MD=6.34, 95%CI: 5.71 to 6.96) was increased in the HIF-PHIs versus those in ESAs. In addition, this study also observed heterogeneity in the ability of HIF-PHIs to decrease hepcidin. Compared with Darbepoetin, only Daprodustat (MD = –49.09, 95% CI: –98.13 to –0.05) could significantly reduce hepcidin levels. Meanwhile, Daprodustat also showed the highest hepcidin-lowering efficacy (84.0%), while placebo was the lowest (8.2%). Conclusion: For NDD-CKD patients, HIF-PHIs could ameliorate functional iron deficiency by promoting iron transport and utilization, which may be achieved by decreasing hepcidin levels. Interestingly, HIF-PHIs had heterogeneous effects on iron metabolism.